Synthesis of 1‐Aminocodeine as a Synthon for Other Codeine Derivatives. Issue 27 (31st July 2013) - Cankař, Petr; Popa, Igor; Trávníček, Zdeněk; Stýskala, Jakub; Hradil, Pavel; Slouka, Jan
Abstract: The first nitration of codeine by using bismuth nitrate pentahydrate under mild reaction conditions is described. The resulting 1‐nitrocodeine was reduced to 1‐aminocodeine, a key precursor for the synthesis of the azo derivative and several hydrazones. Structures of both 1‐nitrocodeine and 1‐aminocodeine were unequivocally determined by single‐crystal X‐ray analysis. The reported preliminary synthetic study lays the groundwork for the synthesis of modified codeine derivatives with potential biological activity. Abstract : The synthesis of 1‐aminocodeine through reduction of 1‐nitrocodeine is described. Nitration was carried out under mild reaction conditions by using bismuth nitrate pentahydrate. Potential applications of 1‐aminocodeine for the synthesis of other codeine derivatives were demonstrated.